Indicators to Monitor Regional Trade Integration in Africa - Walkenhorst, Peter (World Bank, Washington, DC, 2014)
More than 350 Regional Trade Agreements (RTAs) are currently in force and more than one-half of global trade is carried out under preferential terms. A strong set of results based indicators can help to illuminate the costs and benefits of policy initiatives and, thus, inform the broader public dialogue on complementary reforms. The following discussion takes stock of the monitoring practices in Africa with respect to regional trade initiatives and evaluates the need for further indicator development. The assessment thereby focuses on the downstream outcomes of existing trade commitments and the measurement of how regional trade policies affect ordinary traders, producers, and consumers. This spotlight on impact-monitoring for the general population also helps to establish whether decision makers have the necessary tools at hand to evaluate the linkages between regional trade arrangements and poverty reduction. This paper is divided into following sections: section one gives background and motivation for the analysis; section two briefly discusses integration monitoring systems and related indicators in general; section three presents an overview of regional trade indicators that are currently used by policy-makers in sub-Saharan Africa; section four surveys the respective monitoring practices in other regions of the world; and section five provides suggestions for indicator development in Africa based on the practices and gaps identified in the earlier parts of the report.